2021
DOI: 10.1002/jlb.3a0820-522rr
|View full text |Cite
|
Sign up to set email alerts
|

Human monocytes store and secrete preformed CCL5, independent of de novo protein synthesis

Abstract: Monocytes are a subset of circulating peripheral blood mononuclear cells with diverse roles in immunity, including sentinel roles in cytokine secretion. Conventionally, cytokines require an inductive stimulus for their expression and secretion, resulting in a time lag from the time of stimulation to when the proteins are packaged and secreted. Because cytokines are the main communicators in the immune system, their temporal expression is a key factor in coordinating responses to efficiently resolve infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…5B ), we next determined if cytokines can be secreted downstream of the activated transcription factor. The prototypical inflammatory cytokine, TNF-α, is secreted by primary human monocytes and monocytic cell lines upon LPS-induced NF-κB activation ( 59 61 ). To that end, we conducted a similar experiment with LPS-loaded virions overlayed onto THP-1 monocytes and then assayed the culture supernatants for secreted TNF-α ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B ), we next determined if cytokines can be secreted downstream of the activated transcription factor. The prototypical inflammatory cytokine, TNF-α, is secreted by primary human monocytes and monocytic cell lines upon LPS-induced NF-κB activation ( 59 61 ). To that end, we conducted a similar experiment with LPS-loaded virions overlayed onto THP-1 monocytes and then assayed the culture supernatants for secreted TNF-α ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, results from the TLR4 reporter cell line indicated that both NF-κB and IRF3 get activated by CD14 + virions loaded with LPS. Activated NF-κB ( 59 61 ) and IRF3 ( 38 , 62 , 63 ), then, were presumably responsible for the secretion of TNF-α and CCL5, respectively, by THP-1 cells. This rationale was partially confounded by the absence of the canonical IRF3 gene target, IFN-β, being secreted by monocytes and macrophages tested herein.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IL-10 can downregulate MHC class II molecules on monocytes, but specifically HLA-DR on all monocytes and HLA-DM on CD14 + and CD16 + [ 208 ]. Alternative classical monocytes can secrete proinflammatory cytokines such as IL-6, IL-8, and chemokines CCL2, CCL3, and CCL5 [ 209 , 210 ]. Throughout monocyte development, progressive changes in activation and upregulation of CD16 expression can occur with antigen presentation complexes usually accompanied by cytokine secretion of TNF-α, IL-1β, and IL-6 upon TLR stimulation.…”
Section: Inflammatory Cells and Phagocytesmentioning
confidence: 99%
“…We used primary classical monocytes (CD14 + CD16 − , henceforth: “monocytes”) [ 16 ], which account for approximately 92% of all human monocytes [ 17 ]. Monocytes secrete a variety of proteins, including pro-inflammatory cytokines such as IL-1β [ 18 ], anti-inflammatory cytokines such as TGFβ [ 19 ] and chemoattractants for various cell types, such as CXCL8 for neutrophils [ 20 ], or CCL5 that attracts both T-lymphocytes and monocytes [ 21 ] as well as the non-canonical Wnt-5a ligand [ 22 ]. Consequently, monocytes play important roles in immune defense, inflammation, tissue remodeling, and self-recruitment/movement to sites of inflammation, which are all critical for the host defense [ 23 ].…”
Section: Introductionmentioning
confidence: 99%